Management of Lower Respiratory Tract Illnesses in Developing Countries: A Narrative Review - Mohammad Jafar Saffar; Mohammad Sadegh Rezai (Mazandaran University of Medical Sciences, 2014)
Pneumonia is the leading cause of mortality in young children worldwide. Early diagnosis and empiric antibacterial therapy is an important strategy to improve outcome. The World Health Organization has developed case management guidelines to reduce pneumonia-related deaths through early diagnosis and antibiotic treatment. For management purpose, pneumonia is subclassified by its severity. Children with simple pneumonia, pneumonia with chest wall in-drawing or pneumonia with danger signs (convulsion, cyanosis, inability to drink, abnormal sleepiness). Pneumonia with danger signs requires hospitalization and parenteral antibiotics, whereas children who only have fast breathing (tachypnea) can be treated at home with oral antibiotics. Later, these strategies were incorporated into the Integrated Management of Childhood Illnesses, and the protocol was adopted by several developing countries. Despite the proven benefit of this program in reducing pneumonia-related deaths, there has been some concern about the specificity of the World Health Organization and the Integrated Management of Childhood Illnesses guidelines, leading to unnecessary use of antibiotic for children with tachypnea, which were categorized as pneumonia. There is a necessity to improve the Integrated Management of Childhood Illnesses case management of childhood pneumonia because of overlap with other lower respiratory tract illnesses. This review outlines current guidelines for childhood pneumonia management in developing countries and identifies challenges for improvement in management in a variety of settings.